Клинико-эпидемиологическая характеристика гриппа в постпандемический период - Maleev V.V.; Mikhailova E.V.; Chudakova Т.К.; Romanovskaya A.M.; Danilov A.N.; Khripunova G.I.; Dubovitskaya N.A. (Саратовский научно-медицинский журнал, 2013)
Objective: To analyze the clinical and epidemiological characteristics in the post-pandemic influenza seasons in 2010/11/12/13 years. Material and methods: The analysis of the incidence of acute respiratory viral infections and flu in the Saratov region from 2009 to 2013. A clinical and laboratory examination of 252 patients with a diagnosis of «flu»: 152 pregnant women at different stages of pregnancy at the age of 18 years to 41 years and 100 children aged from 5 months to 14 years. The work was carried out to assess the epidemiological pattern and clinical course of influenza, and the effective operation of antiviral therapy. Results: In the post-pandemic period 2010-2013 simultaneously circulating influenza A viruses (N1N1/09) pd, influenza A (H3N2) and influenza B. In most cases, influenza in adults and children is of moderate form. All serious forms of influenza have been caused by influenza A with the development of viral-bacterial pneumonia, respiratory failure and neurotoxic syndrome. Late hospitalization and absence of antiviral therapy in the prehospital are at risk of severe and complicated forms. Conclusion: Early initiation of antiviral therapy is one of the main factors for the effectiveness of treatment and reduce the risk of influenza complications.